Strong negative interference of ethamsylate (Dicynone®) in serum creatinine quantification via enzymatic assay using Trinder reaction - Wiewiorka, Ondrej; Dastych, Milan; Čermáková, Zdenka (Scandinavian journal of clinical and laboratory investigation, 2013)
BACKGROUND: With discrepancies encountered as early as the verification of enzymatic method for quantification of serum creatinine, our research pointed to a later confirmed interference caused by a compound called ethamsylate present in the commonly used antihemorrhagic drug Dicynone. METHODS: We measured concentrations of creatinine of 10 patients with blood taken before and 15 minutes after the intravenous administration of a 500 mg dose of Dicynone. The creatinine concentration was determined using Jaffe method and enzymatic method that utilize Trinder reaction (Roche) in analyzer Cobas c 501 (Roche AG, Basel, Switzerland). We also monitored concentration of blood creatinine in three patients before and 15 minutes after application of Dicynone (500 mg i.v.) and in the following 6th, 12th, 18th, and 24th hours. RESULTS: We discovered a significant negative bias in creatinine results using enzymatic assay with Trinder reaction in blood taken 15 min after i.v. application of 500 mg Dicynone to patients compared to their pre-application values (average decrease of 47%). Unlike this, the results of compensated Jaffe method yielded steady results in all samples (average deviation 0.6% from original values). However, 12 h after the drug administration comparable results were seen as before the administration. CONCLUSION: Considering the strong negative interference of ethamsylate in enzymatic assay using Trinder reaction for creatinine quantification, blood from patients with prescribed Dicynone should be taken at least 12 h after the last application of the drug for obtaining the correct creatinine values.
Keywords: Enzyme Assays; False Negative Reactions; Humans; lidé středního věku; kreatinin; Blood Chemical Analysis; Female; Aged; mladý dospělý; dospělí; falešně negativní reakce; hemostatika; enzymatické testy; senioři; lidé; Creatinine; Adult; Ethamsylate; ženské pohlaví; Male; Middle Aged; Hemostatics; Aged, 80 and over; Young Adult; biochemická analýza krve; senioři nad 80 let; ethamsylát; mužské pohlaví